Análise da estimativa de precipitação PR-TRMM durante a estação chuvosa para os estados e Alagoas e Sergipe - Azevedo, Carlos Denyson da Silva (2015)
Precipitation is one of the most important variable and difficult to measure for the tropical region, especially east coast of Northeast Brazil (NEB), where are located the states of Alagoas (AL) and Sergipe (SE) due to the great lack of rainfall stations . The rainy season for the east coast of the NEB is from April to August and between the main mechanisms that influence in their rush are the wave disturbances in the trade winds, the effects of breeze and remnants of cold fronts. However the region is climbs a subsidence zone due to its adjacency to the Amazon region, with the result that the majority of the rains are coming from clouds of which the ice phase does not contribute significantly in their rush, hot top convective clouds (WRC) and stratiform (STR). Remote sensing techniques (SR) have been used for spatial detection of rain around the globe. However most of the SR techniques is not effective in the rain recovery for WRC and STR, because they are based on top of the clouds, they are geared towards convective cloud cold top (CNV). A milestone in estimating precipitation SR occurred with the radar Release Precipitation Radar (PR) on board the satellite Tropical Rainfall Measuring Mission (TRMM), because the use of active microwave to retrieve the precipitation below the cloud's surface without interference surface echoes, ideal for the WRC. The objective of this research was to conduct an analysis of the estimated rainfall during the rainy season in the AL and SE using TRMM PR-sensor for the period 2004-2013. For this purpose were collected Lat and Lon of each pixel for each run TRMM, and were subsequently passed to a matrix of grid point 0.25°x0.25°, which covers the area 8-12° S and 40-35° O. A priori was held the classification of types of precipitating clouds in the region using the methodology proposed by Awaka et al. (1997). Subsequently were adopted different relationships between the radar reflectivity and precipitation rate (Z-R) proposed in the literature, a general found by Marshall-Palmer (1948) (Z-R MP) and specific for the region developed by Tenório et al (2010) ( Z-R TEN), as well as estimated by the TRMM-PR; to estimate monthly rainfall each month and the monthly average for 2004-2013, the daily cycle of precipitation using the intervals between 00-06h, 06-12h, 12-18h and 18-00h (local time) and the contribution of the types of rainfall during the rainy season. After, the comparison of monthly rainfall rates estimated by the Z-R proposals and obtained by automatic weather stations of the National Institute of Meteorology (INMET) conditional on passage of TRMM calculating the correlation coefficient and the distribution of accumulated frequency between the two variables. Could the analysis of estimated rainfall during the rainy season in AL and SE using PR-TRMM data. As well as a brief analysis of climatological precipitation during 2004-2013, showing satisfactory approaches as the seasonal variability of rainfall reported in the literature. Off computed the average monthly rainfall and its interannual variability, and comparison as the surface data to ZR TEN showed better performance both in coastal areas, transition and semiarid region. Was recovered the daily cycle of precipitation and it was observed that its spatial and temporal distribution varies during their months of the rainy season, rainfall during the morning in the last months of the season focuses more to the coast unlike the first few months. The deeds of breezes were observed in the daily cycle of precipitation, and the night breeze converges with the moisture convergence carried by trade winds. The WRC clouds contribute 45% at the beginning of the rainy season, to 80% at the end of the season for the rains in the region. Based on the results the TRMM PR-even with low temporal resolution, it was shown as a potential sensor for estimating precipitation over the states of AL and SE.